2009
DOI: 10.1128/jvi.00353-09
|View full text |Cite
|
Sign up to set email alerts
|

Theiler's Murine Encephalomyelitis Virus Leader Protein Is the Only Nonstructural Protein Tested That Induces Apoptosis When Transfected into Mammalian Cells

Abstract: Theiler's murine encephalomyelitis virus (TMEV) induces two distinct cell death programs, necrosis and apoptosis. The apoptotic pathway is of particular interest because TMEV persists in the central nervous system of mice, largely in infiltrating macrophages, which undergo apoptosis. Infection of murine macrophages in culture induces apoptosis that is Bax dependent through the intrinsic or mitochondrial pathway, restricting infectious-virus yields and raising the possibility that apoptosis represents a mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 44 publications
5
33
0
Order By: Relevance
“…Fan et al (9) recently reported that transfection of an expression construct of BeAn L into BHK-21 cells and a mouse macrophage cell line led to cell death and apoptosis. Romanova et al (18) found evidence of antiapoptotic activity of EMCV and mengovirus L in infections by these cardioviruses in HeLa cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fan et al (9) recently reported that transfection of an expression construct of BeAn L into BHK-21 cells and a mouse macrophage cell line led to cell death and apoptosis. Romanova et al (18) found evidence of antiapoptotic activity of EMCV and mengovirus L in infections by these cardioviruses in HeLa cells.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that apoptosis triggered by transfection in BHK-21 cells of expression constructs of BeAn L required p53 (9). In order to further investigate this issue, we infected HCT116 colorectal cancer cells that constitutively express p53 or do not express p53.…”
Section: Da L Is Proapoptotic In Hela Cells Following Da Virus Infectmentioning
confidence: 99%
See 1 more Smart Citation
“…The marked difference in CPE between HTCV-UC6 and SAFV-3 (NL2007) may also reflect sequence divergence in the L protein (Fig. 6), which in TMEV has been found to mediate apoptosis in infected cells (8). Furthermore, even in the most susceptible lines, individual cells may differ in their permissivity for viral replication due to factors such as inherent heterogeneity of the cell line or cell culture density.…”
Section: Discussionmentioning
confidence: 99%
“…9 TMEV-L is a multifunctional protein that plays important roles in neurovirulence, anti-interferon (IFN) activity and viral persistence. 8 Furthermore, TMEV-L has a pro-apoptotic activity; 10,11 although, in part, it also has antiapoptotic activity depending on the TMEV strain and the particular cell types, 12 such as encephalomyocarditis virus (EMCV)-L. 13 From these observations, TMEV-L should be a key factor in inducing the pathological changes found after infection of the mouse. TMEV-L has a zinc finger domain in the N-terminus, acidic domain in the middle region and S/T-rich domain in the C-terminus.…”
Section: Introductionmentioning
confidence: 99%